The association between healthy dietary habits and physical fitness among junior high school students: A rural school case study - Moch. Yunus; Yulingga Nanda Hanief; Muhammad Putra Ramadhan; Erika Ayu Sylvianingrum (CV Rezki Media, 2025)
Background: The health conditions of the community, particularly in relation to the physical fitness of junior high school students, require serious attention, especially in rural areas that differ significantly from urban areas. Previous research findings on dietary patterns and physical fitness still show inconsistent results. Objectives: This study aims to investigate the relationship between healthy eating habits and physical fitness among junior high school students residing in rural areas. Methods: This study used a quantitative design with a cross-sectional approach. The research subjects consisted of 27 students from public junior high schools in rural areas, selected through a balanced stratified random sampling process that involved all grade levels. Eating habits were measured using a 24-hour food recall, as it is an effective method for monitoring food intake over a short period. Physical fitness was measured using the Nusantara Student Fitness Test (TKPN), a national standard instrument. Data analysis was performed using descriptive statistics, Spearman's correlation, and linear regression. Results: Most of the study participants were underweight with varied eating patterns. The analysis results showed no significant relationship between physical fitness and healthy eating patterns, as indicated by a correlation coefficient of 0.061 and a p-value of 0.764. The small effect size suggests that eating patterns did not have a significant impact on fitness levels in this group of participants. Conclusions: The study shows that rural junior high school students achieve their physical fitness through exercise and their exercise-rest patterns and their inherited characteristics rather than their diet.